2009
DOI: 10.1007/s11259-009-9317-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intravenous ciprofloxacin on the electrocardiogram of healthy dogs

Abstract: The purpose of this study was to evaluate the electrocardiographic effects of single intravenous dose of ciprofloxacin in dogs. Ten adult cross-breed dogs of both sexes were selected as the sample population. Baseline electrocardiographic values were recorded just before drug administration. Then the dogs received intravenous infusion of ciprofloxacin (10 mg/kg) over the fifteen minutes. The ECGs recorded at 15, 30, 60 and 120 minutes after ciprofloxacin administration. The ECG measurements of heart rate, PR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…Toyoshima et al (2005) used parenteral ciprofloxacin (5-200 mg/kg) and confirmed that this drug is a so called "negative compound" for the QTi. Another study used a continual infusion of ciprofloxacin which produced a significant decrease in the HR with concurrent prolongation of the QTi (Ghaffari and Parsamehr 2009). The authors concluded that the reduction in HR, and not the drug, was the reason for this minimal QTi prolongation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toyoshima et al (2005) used parenteral ciprofloxacin (5-200 mg/kg) and confirmed that this drug is a so called "negative compound" for the QTi. Another study used a continual infusion of ciprofloxacin which produced a significant decrease in the HR with concurrent prolongation of the QTi (Ghaffari and Parsamehr 2009). The authors concluded that the reduction in HR, and not the drug, was the reason for this minimal QTi prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Although such adverse effects are known, there are only a few reports in the veterinary literature linking cardiac toxicity and quinolones (Chanoit et al 2005;Lu et al 2008;Ghaffari and Parsamehr 2009). Enrofloxacin is a veterinary quinolone bactericidal agent that is metabolized approximately by 10-40% to ciprofloxacin in the liver (Boothe et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore these monotonically increasing formulae should be avoided for correcting QTi duration for changes in HR in conscious dogs (Tattersall et al, 2006;Schmitt et al, 2007) , . Despite this fact, veterinary studies have preferred Fridericia's approach to the QTc because it is simple and effective in excluding the effect of HR on QTi in dogs (Hamlin et al, 2004;Koyama et al, 2004;Ghaffari and Parsamehr, 2009) (Figures 2 and 3). HR is nearly independent of the RR interval in dogs.…”
Section: Methods Of Qtc Assessmentmentioning
confidence: 99%
“…Although ciprofloxacin is usually taken 2 or 3 times a day based on the manufacturer's package insert, in fact Effects of the Fluoroquinolone Antibacterial Drug Ciprofloxacin on Ventricular Repolarization in the Halothane-Anesthetized Guinea Pig the recommended clinical daily dose of ciprofloxacin for this purpose is a once a day. However, information is limited regarding the electrophysiological effects of ciprofloxacin in the heart at higher dose ranges in vivo (14). In this study, we precisely assessed the cardiac safety of ciprofloxacin using the halothane-anesthetized guinea pig by recording the monophasic action potential (MAP) of the ventricle (15 -17).…”
Section: Introductionmentioning
confidence: 99%